Analytical model for precast wall equipped with U-shaped steel channel connection. (August 2021) - Vaghei, Ramin; Hejazi, Farzad; Firoozi, Ali Akbar
Abstract: The stability and safety of precast concrete structures furnished with different types of connections has been a focus of researchers and engineers in the recent decade. In this study, the new design for connection of precast walls has been proposed by implementing and installing a pair of U-shape steel channels to each wall as male and female parts and tie to each other using bolts and nuts as a dry joint. The high damping rubber sheet has been implemented within the male and female U-shaped channel in order to dissipate vibration transferring within two precast wall when structure subjected to ground motion. The analytical model is developed in order to implement for numerical simulation of precast reinforced concrete (RC) structure with U-shaped wall connection using finite element method and evaluate the performance of proposed joint as energy dissipation systems for reduction of effect of earthquakes on precast structure. Therefore, the constitutive law and finite element (FE) model for proposed wall connection element have been formulated and the FE algorithm is developed to carry out inelastic analysis for precast RC structures equipped with proposed U-shaped connection under dynamic loading. The values for stiffness of connection were achieved by a series of experimental setup. Experimental results showed that the proposed connection failure mechanisms exception made for the specimen subjected to loading in X-direction for first degree of freedom demonstrates less damage in the connection zone due to huge stiffness of precast wall in that direction. This desired failure mechanism led to semi ductile failure in the structure. Finally, the efficiency of precast wall connections on performance of the RC building was carried during static and dynamic loading.